2022
DOI: 10.1038/s41566-022-01092-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-atom engineering of thermally activated delayed fluorophores for high-performance X-ray imaging scintillators

Abstract: The architectural design and fabrication of low-cost and reliable organic X-ray imaging scintillators with high light yield, ultralow detection limits, and excellent imaging resolution is becoming one of the most attractive research directions for chemists, materials scientists, physicists, and engineers due to the devices' promising scientific and applied technological implications. However, the optimal balance between the X-ray absorption capability, exciton utilization efficiency, and photoluminescence quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 49 publications
3
108
0
Order By: Relevance
“…For instance, researchers recently demonstrated that organic scintillators, materials that convert highenergy X-ray beams into visible photons, have a similar luminescence mechanism with OLEDs to some degree. [124][125][126][127][128][129][130][131][132][133][134] Specifically, the recombination of electrons and holes during scintillation also produces singlet and triplet excitons at a 1 : 3 ratio, emphasizing the importance to harness triplet excitons. Therefore, the endeavours made in the PhOLED community will parallelly benefit the research of organic scintillators.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For instance, researchers recently demonstrated that organic scintillators, materials that convert highenergy X-ray beams into visible photons, have a similar luminescence mechanism with OLEDs to some degree. [124][125][126][127][128][129][130][131][132][133][134] Specifically, the recombination of electrons and holes during scintillation also produces singlet and triplet excitons at a 1 : 3 ratio, emphasizing the importance to harness triplet excitons. Therefore, the endeavours made in the PhOLED community will parallelly benefit the research of organic scintillators.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Organic luminescence materials can be excited not only by UV light but also by bombardment of ionizing radiation (such as X-rays or γ-rays) to achieve radioluminescence (RL). However, traditional organic fluorescence molecules have weak X-ray absorption and inefficient exciton utilization . Recently, some organic phosphorescent materials with efficient triplet exciton harvesting have been designed for the preparation of novel scintillators. , An et al reported the introduction of heavy halogen atoms to achieve high-efficiency radioluminescence of metal-free organic molecules .…”
Section: External Stimulus-responsive Rtp Materialsmentioning
confidence: 99%
“…One interesting family of chromophores that involves the control of different excited states is thermally activated delayed fluorescence (TADF) molecules, which have attracted substantial attention as luminescent materials due to their unique ability to harvest often detrimental triplet states as emissive singlet states through the reverse intersystem crossing process. This phenomenon prolongs the fluorescence lifetime of TADF materials from nanoseconds to microseconds, , making them excellent candidates for several applications as luminescence sensors, organic light-emitting devices (OLEDs), ,,, and more recently, as X-ray imaging materials. However, due to the intricate interplay between the triplet and singlet excited states in TADF, it is challenging to control the optical properties of TADF materials by direct structural modifications, but they can serve as excellent energy and/or electron acceptor units. ,,,,,, Other promising luminescent materials are heterobenzodiazole rings, which have also demonstrated excellent luminescent and photochemical behaviors. Unlike TADF materials, the structures of these organic linkers can be easily altered to achieve different reaction outcomes upon light excitation, and they can serve as energy/electron donors in a variety of chemical composites. ,, Moreover, this kind of organic linker is designed to be an easy building block of metal–organic frameworks (MOFs) that can serve not only to improve the optical properties of MOFs but also to favor and increase the efficiency of energy transfer processes at the donor–acceptor interface due to the highly ordered structure of the frameworks. These properties have been exploited in sensing, , catalysis, and light-harvesting applications, i...…”
Section: Introductionmentioning
confidence: 99%